Association of Insomnia with Anxiety and Depression in Type 2 Diabetic Patients: A Cross-Sectional Study - Karlyghash Shinalieva; Asemgul Kasenova; Zauresh Akhmetzhanova; Dinara Alzhanova; Laura Eszhanova; Ainur Bekenova (Iranian Journal of Medical Sciences, 2023)
Background: Type 2 diabetes mellitus (T2DM) is associated with sleep disorders, which in turn may lead to anxiety and depression. Sleep deprivation impairs glucose metabolism causing a decrease in insulin sensitivity and glucose tolerance. The present study aimed to determine the association of insomnia with anxiety and depression in patients with T2DM.Methods: A cross-sectional study was conducted in 2020 at the Endocrinological Department of City Clinical Hospital №1, affiliated with Astana Medical University (Astana, Kazakhstan). A total of 376 patients with decompensated T2DM were included in the study. Insomnia was assessed using the Pittsburgh Sleep Quality Index (PSQI) and Insomnia Severity Index (ISI). Anxiety and depression were assessed using the Hospital Anxiety and Depression Scale (HADS). Multivariable logistic regression was used to assess the association of insomnia with anxiety and depression.Results: All patients showed signs of sleep disturbances. Based on the HADS cutoff score >8, anxiety and depression were observed in 48 (12.80%) and 46 (12.20%) patients, respectively. PSQI, ISI, and HADS indicators were associated with an increased risk of anxiety and depression symptoms. In terms of anxiety, the adjusted odds ratio for PSQI and ISI scores were 1.09 (P=0.08) and 1.07 (P=0.01), respectively. These for depression were 1.10 (P=0.06) and 1.07 (P=0.01), respectively.Conclusion: Sleep quality is an important indicator of psychological health in patients with T2DM, especially those who exhibit signs of anxiety and depression.